Assessment of Nutritional Status Using Composite Index of Anthropometric Failure (CIAF) Among Under-Five Children from An Urban Slum of Southern India: A Cross-Sectional Study: - Mohandas, Anu; Bhuchakra, Hamsa Priya; Varma, Pavani; Pattnaik, Snigdha (National Journal of Community Medicine, 2023)
Introduction: NFHS-5 Telangana reports underweight, stunting, and wasting among under 5 children as 31.8%, 33.1%, and 21.7% respectively. Composite Index of Anthropometric Failure is an aggregate indicator that excludes children with anthropometric failure and includes children who are wasted, stunted, or underweight, and their combinations. The objectives were to determine the prevalence of anthropometric failures and to find its determinants among under-five children in an urban slum area of Hyderabad. Methodology: A cross sectional study was conducted among 310 under 5 children residing in the urban-slum area of Hyderabad. Probability proportionate to size sampling was used. Using questionnaire and standard operating procedures, socio-demographic profile, health details and nutritional assessment was done. Statistical analysis was done using SPSS version 26. Results: The prevalence of anthropometric failure is noted to be 39.6%. The prevalence of stunting, underweight and wasting were found to be 20.7%, 26.8% and 12%, respectively. The illiteracy of father [AOR:2.94(CI: 1.31-6.62); p-value=0.009], low birth weight [AOR:2.024(CI: 1.253-3.26); p-value=0.004], not exclusively breastfed [AOR:4.291(CI:1.55-11.904); p-value=0.005] and deficient calorie intake [AOR: 2.079(CI:1.103-3.906); p-value=0.023] were found to be the significant predictors of Anthropometric failure. Conclusion: Under nutrition is an important public health problem with 40% prevalence in urban slum of Telangana. Enhancing the literacy of fathers, reduction in low birth weight, better IYCF practices and providing calorie adequate diet will aid in enhancing children's nutritional status.